Fibrin deposition on bovine pericardium tissue used for bioprosthetic heart valve drives its calcification - Poitier, Bastien; Rancic, Jeanne; Richez, Ulysse; Piquet, Julie; El Batti, Salma; Smadja, David M. (Frontiers in Cardiovascular Medicine, 2023)
Background: Bioprosthetic heart valves (BHVs) are less thrombogenic than mechanical prostheses; however, BHV thrombosis has been proposed as a risk factor for premature BHV degeneration. Objectives: We aimed to explore whether fibrin deposition on bovine pericardium tissue could lead to calcification. Method: Fibrin clot was obtained by blending three reagents: Cryocheck™ Pooled Normal Plasma (4/6), tissue factor + phospholipids (Thrombinoscope BV), and calcium 100 mM (1/6), and deposited on pericardium discs. Non-treated bovine pericardium discs and fibrin-treated bovine pericardium discs were inserted into the subcutaneous tissue of 12-day-old Wistar rats and sequentially explanted on days 5, 10, and 15. Calcium content was measured with acetylene flame atomic absorption spectrophotometry. Histological analysis was performed using Hematoxylin-Eosin, Von-Kossa staining, and immunohistochemistry. Results: Calcification levels were significantly higher in fibrin-treated bovine pericardium discs compared to non-treated bovine pericardium discs (27.45±23.05 µg/mg vs. 6.34±6.03 µg/mg on day 5; 64.34±27.12 µg/mg vs. 34.21±19.11 µg/mg on day 10; and 64.34±27.12 µg/mg vs. 35.65±17.84 µg/mg on day 15; p<0.001). Von Kossa staining confirmed this finding. In Hematoxylin-Eosin staining, the bovine pericardium discs were more extensively and deeply colonized by inflammatory-like cells, particularly T lymphocytes (CD3 + cells), when pretreated with fibrin. Conclusion: Fibrin deposition on bovine pericardium tissue treated with glutaraldehyde, used for BHV, led to increased calcification in a rat model. BHV thrombosis could be one of the triggers for calcification and BHV deterioration.